Design of a zero‐voltage‐switching large‐air‐gap wireless charger with low electric stress for electric vehicles. Issue 9 (1st November 2013) - Duan, Chen; Jiang, Chenguang; Taylor, Allan; Bai, Kevin (Hua)
Abstract : This study proposes a design and development of a wireless power transfer system to charge the battery in electric vehicles. A parallel–parallel topology is adopted to realise 10–15 cm‐distance power transfer using the resonance theory. Finite‐element method is used to extract the coil parameters. The advantages of the proposed design compared with the previous similar research are (i) low operational frequency (42 kHz) which avoids the electromagnetic interference to the on‐board automotive electronics equipment and (ii) low electric stress to the semi‐conductor switches through using zero‐voltage‐switching technique. A 2 kW prototype to charge 200 V battery was built to experimentally verify the theoretical analysis. The overall system efficiency is ∼ 86%.